Hospitalisation rates in patients switched from oral anti-psychotics to aripiprazole once-monthly for the management of schizophrenia. (July 2013) - Kane, John M.; Sanchez, Raymond; Zhao, Joan; Duca, Anna R.; Johnson, Brian R.; McQuade, Robert D.; Eramo, Anna; Baker, Ross A.; Peters-Strickland, Timothy
Abstract Objective: To report the design and preliminary results of a mirror-image study comparing total psychiatric hospitalisation rates pre- and post-switch to aripiprazole once-monthly, an extended release injectable solution. Methods: A multi-center, open-label mirror-image study of patients (18–65 years) with schizophrenia to compare total psychiatric hospitalisation rates between retrospective treatment with oral standard-of-care (SOC) anti-psychotics and prospective treatment with aripiprazole once-monthly in a naturalistic community setting in North America. Total psychiatric hospitalisation rates were assessed between retrospective (Months −4 to −1) and prospective treatment periods (Months 4–6) for patients who completed ≥3 months aripiprazole once-monthly. Results: One hundred and eighty-three patients entered the prospective phase. After switching to aripiprazole once-monthly, total psychiatric hospitalisation rates for the 3-month prospective period were significantly lower (p < 0.0001, Exact McNemar's test) compared with the retrospective 3-month period when the same patients received SOC anti-psychotics (6.6% [n = 8/121] vs 28.1% [n = 34/121], respectively; rate ratio = 0.24). Similarly, total psychiatric hospitalisation rates for all patients who entered the prospective treatment phase were significantly lower (p < 0.0001, Exact McNemar's test) for the prospective 6 months following switch to aripiprazole once-monthly, compared with the retrospective 6-month SOC period (14.2% [n = 26/183] vs 41.5% [n = 76/183], respectively; rate ratio = 0.34). Common treatment-emergent adverse events (occurring in ≥5% of patients) were psychotic disorder (7.7%), akathisia (7.2%), and insomnia (7.2%). Discontinuation (all causes) during the prospective phase was 44.8% (n = 82/183). Limitations: Mirror-image studies do not include a parallel active control; as each patient serves as their own control, it cannot be determined whether other treatments may have similar effects. Treatment and trial effects may be difficult to separate. Independent factors such as admission patterns, insurance coverage, availability of hospital beds, and community support may influence rates of hospitalisation. Conclusions: Switching to aripiprazole once-monthly substantially reduced total psychiatric hospitalisation rates compared with retrospective rates in the same patients taking oral SOC.